Esophageal variceal ligation plus sclerotherapy vs. ligation alone for the treatment of esophageal varices - Yue, Xiaofen; Wang, Zeyu; Li, Jianbiao; Guo, Xiaoling; Zhang, Xiehua; Li, Shengnan; Lv, Hongcheng; Hu, Dongsheng; Ji, Xiangjun; Li, Shuang; Lu, Wei (Frontiers in Surgery, 2022)
Background. To evaluate the efficacy and adverse events of esophageal variceal ligation (EVL) versus EVL combined with endoscopic injection sclerosis (EIS) in the therapy of esophageal varices. Methods. Patients from January 2017 to August 2021 who received EVL alone (control group) or EVL plus EIS (intervention group) were enrolled in this retrospectively study. Efficacy, including rebleeding (clinically hematemesis or melena, confirmed by endoscopy as esophagogastric varices bleeding), variceal recurrence rate (the presence of esophagogastric varices which is need to be treated again) the number of sessions performed to complete eradication of varices, and safety (adverse events) were compared. The variceal recurrence associated factors were derived by unitivariate and multivariate logistic regression analyses. Results. The variceal recurrence and rebleeding rate in intervention group showed significantly lower than control group (20.7% vs 37.5%, P = 0.029 and 2.6% vs 10.3%, P = 0.006 respectively in the 12-month follow up). The adverse events (fever, chest pain, swallow and esophageal stricture) showed no significant difference between two groups (P＞0.05). Further research showed that efficacy of intervention group better than control group only achieved in prophylactically endoscopic treatment patients. Diameter of esophageal varices and gastric varices co-exist showed significantly effects on variceal recurrence of intervention group (HR=15.856; 95% CI 1.709 - 160.143; P = 0.016 and HR=4.5; 95% CI 1.42 - 20.028; P = 0.021; respectively) . Conclusions. The intervention group may obtain lower recurrence, rebleeding rate and fewer number of sessions performed to complete eradication of varices (number of sessions) and similar incidence of adverse events, especially for prophylactically treatment. Among intervention group, diameter of esophageal varices and gastric varices were closely associated with variceal recurrence.